Sked. Britain’s Decline - Problems and Perspectives - Tate, Roger (Teaching History: A Journal of Methods, 1991)
Perhaps it is inevitable that the nation that gave us Edward Gibbon should have a preoccupation with "decline." In this slender pamphlet, Alan Sked summarizes what three dozen social scientists have said about contemporary Britain’s economic and moral decline. Sponsored by the Historical Association, the pamphlet is designed to inform the average citizen and lift the level of public debate on such issues as the power of trade unions, the Welfare State, crime, drugs, sexual behavior, the Church of England, and low economic productivity. Sked tries to be even-handed in his evaluations, neither attacking nor endorsing the controversial policies of Mrs. Thatcher.